Study Penggunaan Steel-Based Hybrid Sanwich Plate ASTM A36 dengan Core Material Polyurethane Elastomer pada Konstruksi Kapal - Heni Siswanti; Muhammad Musta'in; Tristiandinda Permata; Arisessy Mulananda (POLITEKNIK NEGERI BENGKALIS, 2022)
Conventional ship structures usually consist of a stiffened plate. The intersection of the secondary stiffener of the stiffened plate structure is the critical position with a high potential for structural damages such as fatigue crack. The recent development of material technology in the marine industry is how to find the strength and lightweight material and also minimize structural problems such as fatigue cracks. One of them is the application of sandwich plates to replace the stiffened plate construction. Steel-based hybrid sandwich plates consist of two steel faceplates and elastomer core material bonded by adhesive. This study has analyzed the application of steel-based hybrid sandwich plates to replace stiffened plates on the oil tanker’s inner bottom structure. The strength of three configurations of the inner bottom sandwich structure has been analyzed by using the Finite Element Method and compared to conventional stiffened plate structure. The maximum stress, average stress, maximum deformation, and weight of the structure have been compared and analyzed. The results show that the application of a hybrid sandwich with a certain stiffener configuration can reduce stress, deformation, and weight of the inner bottom structure.